Fast and ejficient microwave-assisted synthesis of CaTiO3 - De Cássia Pereira, Sandra; De Figueiredo, Alberthmeiry T.; Barrado, Cristiano M.; Stoppa, Marcelo H.; Dos Santos, Tatiane O.; Pontes, Fenelon M. [UNESP]; Longo, Elson [UNESP] (IOP Publishing, 2017)
The traditional methods to synthesize nanocrystalline materials are energy-intensive and time-consuming. This paper describes a fast and simple route to synthesize CaTiO3, which requires just 30 s of processing in the HTMW system to produce the crystalline orthorhombic phase of CT with a micro-cube-like structure. The product's crystallinity increases along with synthesis time. A correlation is identified between microwave processing time and structural crystallinity.
Keywords: CaTiO3; Cube-like structure Supplementary material for this article is available online; Microwave synthesis; XANES